Examining the Effect of Teachers' School Climate Attitudes on Classroom Management Styles (Journal of Management and Educational Sciences, 2024)
This study aims to examine the effects of teachers' perceptions of school climate on classroom management styles according to teachers' opinions. This study was conducted with a relational screening model. According to the research results; it is seen that teachers' perceptions of school climate and classroom management styles are above average. In the examination according to gender; male teachers' perception of classroom management is higher than female teachers. On the other hand, it was revealed that the perception of school climate does not change according to female or male teachers. In the examination according to marital status; classroom management styles and school climate scales do not change according to married or single status. In the examination according to educational status; in the general dimension of school climate, the perceptions of school climate of teachers with bachelor's degree were higher than those with postgraduate degrees. On the other hand, it was revealed that the perceptions of classroom management styles do not change according to bachelor's or master's degree graduation status. In the examination according to age groups; classroom management styles and school climate perceptions do not change according to age groups. In the examination according to year of service groups; classroom management styles and school climate perceptions do not change according to year of service groups. There is no statistically significant relationship between the participants' perceptions of school climate total scores and classroom management styles total scores. In addition, school climate total scores do not significantly predict classroom management styles total score perceptions.